2017
DOI: 10.1016/j.exphem.2016.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by MLL fusion proteins in leukemogenesis

Abstract: Chromosomal translocations involving the mixed lineage leukemia (MLL) gene cause aggressive leukemia. Fusion proteins of MLL and a component of the AF4 family/ENL family/P-TEFb complex (AEP) are responsible for two-thirds of MLL-associated leukemia cases. MLL-AEP fusion proteins trigger aberrant self-renewal of hematopoietic progenitors by constitutively activating self-renewal-related genes. MLL-AEP fusion proteins activate transcription initiation by loading the TATA-binding protein (TBP) to the TATA element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 110 publications
(165 reference statements)
0
36
1
Order By: Relevance
“…However, we note that 12 of our patients have not been genotyped for MLL translocation. Nevertheless, this suggests that MLL translocations may induce a unique epigenetic state that dominates the overall enhancer landscape of the given AML sample, not surprising given the function of MLL fusion proteins in mis-regulating DOT1L function leading to aberrant histone H3K79 methylation (27). While mutations in NPM1 and FLT3 are enriched in clusters 2, 3, 4, and 6, no cluster-specific associations were observed for mutations in DNMT3A , TET2 , and IDH1 and IDH 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, we note that 12 of our patients have not been genotyped for MLL translocation. Nevertheless, this suggests that MLL translocations may induce a unique epigenetic state that dominates the overall enhancer landscape of the given AML sample, not surprising given the function of MLL fusion proteins in mis-regulating DOT1L function leading to aberrant histone H3K79 methylation (27). While mutations in NPM1 and FLT3 are enriched in clusters 2, 3, 4, and 6, no cluster-specific associations were observed for mutations in DNMT3A , TET2 , and IDH1 and IDH 2.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of menin has been shown to coincide with the loss of H3K4me3 at specific genes, and at the same genes, gain of H3K27me3 that is an epigenetic mark of gene repression (Agarwal and Jothi 2012; Lin, et al 2015; Scacheri, et al 2006). MLL1 gene (chromosome 11q23) translocation with several different genes that encode transcription factors leads to the formation of MLL1-fusions that activate the expression of genes such as the HOX genes that cause leukemia (Yokoyama 2017). The interaction of menin in the Trithorax-like MLL protein complex has shown that menin is essential in this complex for the oncogenic activity of MLL1-fusion proteins to cause leukemia (Hughes, et al 2004; Yokoyama, et al 2005).…”
Section: An Unexpected Function Of Menin As a Pro-oncogenic Factor Inmentioning
confidence: 99%
“…Multiple studies reported that these alternations can affect transcriptional activity, resulting in cancer development 2 . Chromosomal abnormality also affects tumor malignancy, as these abnormalities frequently result in formation of fusion genes with TFs that activate oncogenic signaling pathways 3 …”
Section: Introductionmentioning
confidence: 99%